Voices from the last mile the place of emotions in the social impact analysis of access to communication - Dionisio, Josephine C.; Evangelista, John Andrew G.; Heimerl, Kurtis; Festin, Cedric Angelo M. (2021)
Access online through this link: https://www.plarideljournal.org/article/voices-from-the-last-mile-the-place-of-emotions-in-the-social-impact-analysis-of-access-to-communication
Keywords: Social impact assessment; Technology and society; Mobile communication systems